2008
DOI: 10.1080/01904160802463130
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic Difference in Arsenic and Cadmium Accumulation by Rice Seedlings Grown in Hydroponics

Abstract: Genotypic differences in arsenic (As) and cadmium (Cd) uptake and their translocation within rice seedlings grown in solution culture were investigated. Arsenic uptake and its translocation differed significantly between eight cultivars. The largest shoot and root As concentrations were found in cultivar 'TN1' and 'ZYQ8', while cultivar 'JX-17' had the lowest As concentration. Arsenic concentration in shoot or root of 'JX-17' was about 50% of that in cultivar 'ZYQ8'. Specific Arsenic uptake (SAU) was found sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 50 publications
2
21
0
Order By: Relevance
“…The largest arsenic concentrations in root and vegetative parts were found in cultivar 'TN1' and 'ZYQ8', while cultivar 'JX-17' had the lowest arsenic concentration. Arsenic concentration in shoot or root of 'JX-17' was about 50% of that in cultivar 'ZYQ8' [93].…”
Section: Genotype Variation In Ricementioning
confidence: 91%
“…The largest arsenic concentrations in root and vegetative parts were found in cultivar 'TN1' and 'ZYQ8', while cultivar 'JX-17' had the lowest arsenic concentration. Arsenic concentration in shoot or root of 'JX-17' was about 50% of that in cultivar 'ZYQ8' [93].…”
Section: Genotype Variation In Ricementioning
confidence: 91%
“…Selection and breeding of rice cultivars with low As and Cd accumulation have been practiced to reduce As and Cd in the rice grains (Zhang and Duan, 2008;Li et al, 2012;Ye et al, 2012). Water management is another promising method that affects Cd and As bioavailability in soils and their subsequent uptake by rice (Arao et al, 2009;Rahaman et al, 2011;Hu et al, 2013b).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have confirmed that different varieties of rice have different capacities to accumulate Cd and As from the soil (Yu et al 2006;Zhang and Duan 2008;Yan et al 2010). Selection and breeding of rice varieties with low Cd and As accumulation is important for lowering Cd and As risks (Zhang and Duan 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have confirmed that different varieties of rice have different capacities to accumulate Cd and As from the soil (Yu et al 2006;Zhang and Duan 2008;Yan et al 2010). Selection and breeding of rice varieties with low Cd and As accumulation is important for lowering Cd and As risks (Zhang and Duan 2008). Efforts have been made to lower metal concentrations in rice and metal toxicity by changing metal availability in the soil to produce safer food (Li et al 2009;Fan et al 2010;Gu et al 2011).…”
Section: Introductionmentioning
confidence: 99%